Defect Engineering with Rational Dopants Modulation for High-Temperature Energy Harvesting in Lead-Free Piezoceramics - Xi, Kaibiao; Guo, Jianzhe; Zheng, Mupeng; Zhu, Mankang; Hou, Yudong (Nano-Micro Letters, 2024)
High temperature piezoelectric energy harvester (HT-PEH) is an important solution to replace chemical battery to achieve independent power supply of HT wireless sensors. However, simultaneously excellent performances, including high figure of merit (FOM), insulation resistivity (ρ) and depolarization temperature (Td) are indispensable but hard to achieve in lead-free piezoceramics, especially operating at 250 °C has not been reported before. Herein, well-balanced performances are achieved in BiFeO3–BaTiO3 ceramics via innovative defect engineering with respect to delicate manganese doping. Due to the synergistic effect of enhancing electrostrictive coefficient by polarization configuration optimization, regulating iron ion oxidation state by high valence manganese ion and stabilizing domain orientation by defect dipole, comprehensive excellent electrical performances (Td = 340 °C, ρ250 °C > 107 Ω cm and FOM250 °C = 4905 × 10–15 m2 N−1) are realized at the solid solubility limit of manganese ions. The HT-PEHs assembled using the rationally designed piezoceramic can allow for fast charging of commercial electrolytic capacitor at 250 °C with high energy conversion efficiency (η = 11.43%). These characteristics demonstrate that defect engineering tailored BF-BT can satisfy high-end HT-PEHs requirements, paving a new way in developing self-powered wireless sensors working in HT environments. Highlights: 1 The solution limit of manganese ion in BiFeO3–BaTiO3 (BF–BT) was determined by combining multiple advanced characterization methods. 2 The defect engineering associated with fine doping can realize the co-modulation of polarization configuration, iron oxidation state and domain orientation. 3 The BF–BT–0.2Mn piezoelectric energy harvester shows excellent power generation capacity at 250 °C, which is an important breakthrough for lead-free piezoelectric devices.